Geoelectrical prospection of disseminated sulfide mineral occurrences in Camaquã Sedimentary Basin, Rio Grande do Sul State, Brazil - Moreira, César Augusto [UNESP]; Lopes, Syngra Machado [UNESP]; Schweig, Camila [UNESP]; Seixas, Adriano da Rosa [UNESP] (My University, 2012)
The mineral exploration is a complex activity that should involve a combination of direct and indirect techniques of geological investigation. The growing demand for base metals in the national and international market provides the revaluation of mineral occurrences that can become deposits and mines. This paper presents the results of the electrical resistivity and induced polarization geophysical methods in azimuthal arrangement, applied in a mineral occurrence of disseminated copper sulfides, previously studied through trenches and core drilling, located in the Camaquã Sedimentary Basin, Rio Grande do Sul State, Brazil. The inversion models indicate the coincidence of high chargeability and low resistivity values. The integration of geophysical data permitted the elaboration of 3D attributes visualization models for the mineralization enclosed in volcanic tuffs. The integrated geophysical and geological analysis indicates the potential of a new mineralized area. © 2012 Sociedade Brasileira de Geofísica.
Keywords: Copper; Geophysics; Modeling; Ore; Sulfide; azimuth; copper compound; core logging; electrical resistivity; geoelectric field; geophysical survey; induced polarization; mineral exploration; mineralization; ore deposit; sedimentary basin; sulfide; tuff; Brazil; Camaqua Basin; Rio Grande do Sul